The contribution of goal specificity to goal achievement in collaborative goal setting for the management of asthma - Smith, L.; Alles, C.; LeMay, K.; Reddel, H.; Saini, B.; Bosnic-Anticevich, S.; Emmerton, Lynne; Stewart, K.; Burton, D.; Krass, I.; Armour, C. (Elsevier Inc., 2013)
Background: Goal setting was investigated as part of an implementation trial of an asthma management service (PAMS) conducted in 96 Australian community pharmacies. Patients and pharmacists identified asthma-related issues of concern to the patient and collaboratively set goals to address these. Although goal setting is commonly integrated into disease state management interventions, the nature of goals, and their contribution to goal attainment and health outcomes are not well understood. Objectives: To identify and describe: 1) goals set collaboratively between adult patients with asthma and their pharmacist, 2) goal specificity and goal achievement, and 3) describe the relationships between specificity, achievement, asthma control and asthma-related quality of life. Methods: Measures of goal specificity, and goal achievement were developed and applied to patient data records. Goals set were thematically analyzed into goal domains. Proportions of goals set, goals achieved and their specificity were calculated. Correlational and regression analyses were undertaken to determine the relationships between goal specificity, goal achievement, asthma control and asthma-related quality of life.Results: Data were drawn from 498 patient records. Findings showed that patients set a wide range and number of asthma-related goals (N = 1787) and the majority (93%) were either achieved or being working toward by the end of the study. Goal achievement was positively associated with specific and moderately specific goals, but not non-specific goals. However, on closer inspection, an inconsistent pattern of relationships emerged as a function of goal domain. Findings also showed that goal setting was associated with end-of-study asthma control but not to asthma-related quality of life. Conclusions: Pharmacists can help patients to set achievable and specific asthma management goals, and these have the potential to directly impact health outcomes such as asthma control. Goal specificity appears to be an important feature in the achievement of goals, but other factors may also play a role.